Representation of robotic fractional dynamics in the pseudo phase plane - Lima, Miguel F. M. (2011)
This paper analyses robotic signals in the perspective of fractional dynamics and the pseudo phase plane (PPP). It is shown that the spectra of several experimental signals can be approximated by trend lines whose slope characterizes their fractional behavior. For the PPP reconstruction of each signal, the time lags are calculated through the fractal dimension. Moreover, to obtain a smooth PPP, the noisy signals are filtered through wavelets. The behavior of the spectra reveals a relationship with the fractal dimension of the PPP and the corresponding time delay.